Uso de avisos para la explotación y la trata de jóvenes en América Latina (2015)
This article presents an interpretative analysis of the resultsof the investigations carried out from the organizations ofcivil society, the State and the academy in Mexico, Argentina,Bolivia, and Colombia, whose object of study has been noticeswith and without sexual content used to attract young peopleto the exploitation and trafficking. It shows answers to basicquestions from the functionalist models, and structuralismcritic of social communication, such as: What is the relationshipbetween classified ads and sexual slavery? Who use and whatis the purpose of using classified ads with and without sexualcontent? Where is the source of this type of investigationsand what is the reason for carrying them out? What type ofanalysis methodologies are used to make the interpretation ofthis phenomenon? What results have been obtained? What arethe challenges those investigations impose on us? This articleoffers a characterization of the modus operandi or the way howit behaves capturing youngsters through mass, alternative, andinformal media in pro of the prevention to vulnerable victims.In the same way, it makes strategies developed by each of theagents that act against trafficking in persons available.